The Development of a Book of Folklore Enrichment of Java Language Learning Resources in Kebumen District - Sari, Rina Kurnia (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2018)
Abstrack Folklore is a learning of java language contained in the curriculum 2013. Javanese language teachers are still dificult to find a source of learning folklore legend in Kebumen district.Lack of teching material of folklore legend and less interest of students in studying folklore make folklore legend in regency Kebumen feasible to be developed. Based on the questionnaire of the needs of teachers and students, folklore book â€œFolklore Regency Kebumenâ€ in accordance with the title and purpose of making that use java language. The book is in terms of story content, design, and image arrangement is feasible to be used based on the assessment of material and user media experts. Keyword: enrichment books; folklore; legend